Serum Troponin-I Levels Facilitate Early Prediction of Cardiac Toxicity among High-Risk Patients Under Chemotherapy with Doxorubicin (Mugda Medical College Journal, 2026)
A quasi-experimental study was conducted in the Department of Medical Oncology, National Institute of Cancer Research & Hospital (NICRH), Dhaka, Bangladesh, between September 2021 to August 2022, to evaluate troponin-I level as a biomarker to detect early-onset of cardiotoxicity among patients under chemotherapy with doxorubicin. We included patients having any malignancy (histopathologically confirmed) and receiving a dose of doxorubicin 45–75 mg/m² BSA 3 weekly in each cycle of chemotherapy. Exclusion criteria were: patients aged 70 years, having pre-treatment level of troponin-I >0.08 ng/ml, any preexisting cardiac disease detected through echocardiography, any significant change in ECG before treatment except sinus tachycardia, known case of hypertension, diabetes mellitus, chronic renal failure, chronic liver disease, obesity (BMI ³25), previous exposure to chemotherapy or radiotherapy and WHO performance status 3 to 4. However, a non-probability, convenient and purposive sampling technique was adopted. A total of 71 patients were finally enrolled in this study. Multiple assessment were done at baseline and after 3 and 6 cycles of chemotherapy, which included systemic examination, laboratory investigations including complete blood count (CBC), serum troponin-I level, chest radiograph, ECG, echocardiography, ultrasonogram of the whole abdomen and CT scan/MRI, if needed. The mean age of the patients was 32.97±14.1 years. Most of the patients were in the 18–30 years age group (49.4%), followed by 31–40 years age group (22.5%) and 41–50 years age group (15.5%). A male predominance was observed; male-female ratio was 1.63:1. Cardiac toxicity was present in 21(29.6%) patients and absent in 50(70.4%) patients (403.71±42.358 mg/m2 BSA vs. 368.36±44.53 mg/m2 BSA of mean cumulative dose of doxorubicin; p